Convergence in the Cesàro sense of ergodic operators associated with a flow. - Bernardis-Medici, Ana Lucía; Martín-Reyes, Francisco Javier; Sarrion-Gavilán, María Dolores (My University, 2000)
We study the a.e. convergence ofthe Ceshro-(1 +c) ergodic averages and the a.e. existence in the Ceso-u sense ofthe ergodic Hilbert transform associated with a Cesobounded flow and < c < 0.
Política de acceso abierto tomada de https://ijm.math.illinois.edu/online-access/
Keywords: Flujos (Sistemas dinámicos diferenciables); Ergodic operators; Convergence in the Cesáro sense